Emerging technologies in digital manufacturing and smart factories - Hassan, Ahdi 1991-; Dutta, Pushan Kumar 1985-; Gupta, Subir 1976-; Mattar, Ebrahim 1964-; Satya Singh 1979- (Advances in logistics, operations, and management science (ALOMS) book series, 2024)
Rapid digital transformation is forcing the manufacturing industry to drastically alter its current trajectory for future success. The remarkable convergence of digitalization and manufacturing is reshaping industries, ushering in an era known as Industry 5.0. This revolutionary transition has given birth to digital manufacturing and smart factories, heralding a new dawn in the way we produce goods. The amalgamation of artificial intelligence (AI), robotics, the internet of things (IoT), augmented reality (AR), virtual reality (VR), big data analytics, cloud computing, and additive manufacturing stands poised to unlock unprecedented avenues in the realm of production.Practitioners, researchers, dreamers, and pioneers all are beckoned to explore the uncharted territories of digital innovation in manufacturing. Emerging Technologies in Digital Manufacturing and Smart Factories spans domains from mechanical and electrical engineering to computer science, from industrial economics to business strategy, and this book addresses this diverse audience. The book embarks on a comprehensive voyage, unveiling the latest evolutions and nascent trends within digital manufacturing and smart factories. From inception to execution, from design optimization to predictive maintenance, every phase of the manufacturing lifecycle is scrutinized through the lens of cutting-edge technologies. Rather than relying exclusively on the theoretical realm, this book also ventures into the crucible of real-world application, offering practical insights drawn from varied industries, including automotive, aerospace, and pharmaceuticals.